Same, Same but Different: Proportionality Assessments and Equality Norms - Anna Nilsson (Oslo Law Review)
Proportionality reasoning is an established form of legal argumentation under international human rights law, employed by the European Court of Human Rights and the United Nations (UN) human rights treaty bodies alike. However, relatively little has been written about its precise role and content in relation to equality norms. Proportionality scholars tend to draw on other examples to demonstrate how proportionality reasoning works in practice, and legal scholarship on equality and non-discrimination has not fully explored whether or how proportionality argumentation can assist us in distinguishing lawful state practices from unlawful ones. This article picks up these loose ends and develops a model of proportionality assessment tailored to the non-discrimination context. The model breaks down proportionality argumentation into a step-by-step process and sets out clear criteria to be fulfilled at each step. It illustrates the distinctive features of balancing as a part of discrimination analysis and provides useful guidance to national authorities tasked with such balancing. It is anchored in existing non-discrimination jurisprudence but structured so as to facilitate more predictable outcomes than existing justification tests.